2015
DOI: 10.1128/jcm.02012-15
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Mycobacterium tuberculosis of the Latin American Mediterranean Lineage, Wrongly Identified as Mycobacterium pinnipedii (Spoligotype International Type 863 [SIT863]), Causing Active Tuberculosis in South Brazil

Abstract: We recently detected the spoligotype patterns of strains of Mycobacterium pinnipedii, a species of the Mycobacterium tuberculosis complex, in sputum samples from nine cases with pulmonary tuberculosis residing in Porto Alegre, South Brazil. Because this species is rarely encountered in humans, we further characterized these nine isolates by additional genotyping techniques, including 24-locus mycobacterial interspersed repetitive-unit-variable-number tandem-repeat (MIRU-VNTR) typing, verification of the loci T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…Interestingly, the SIT863/PINI2 strains underwent diversification at locus 154 (154_2). The phylogenetic positioning of SIT863/PINI2 in the RD115-sublineage is congruent with previous data on its SNP barcode lineage (4.3.3) as a RD115 sub-lineage branch (Coll et al, 2014; Dalla Costa et al, 2015). Nevertheless, some phylogenetic incongruences were noted as other unrelated strains, e.g., Beijing or T1, were included in this branch, thus exemplifying the problem of MIRU-VNTR convergence.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, the SIT863/PINI2 strains underwent diversification at locus 154 (154_2). The phylogenetic positioning of SIT863/PINI2 in the RD115-sublineage is congruent with previous data on its SNP barcode lineage (4.3.3) as a RD115 sub-lineage branch (Coll et al, 2014; Dalla Costa et al, 2015). Nevertheless, some phylogenetic incongruences were noted as other unrelated strains, e.g., Beijing or T1, were included in this branch, thus exemplifying the problem of MIRU-VNTR convergence.…”
Section: Resultssupporting
confidence: 88%
“…Thirty-one isolates were also found to form a monophyletic branch containing the 154_1 allele as a marker for the RD115 sublineage. This branch included, among others, the “ pinnipedii -like” strains SIT863/PINI2 which has been shown by some of us to in fact belong to the LAM lineage (Dalla Costa et al, 2015). Interestingly, the SIT863/PINI2 strains underwent diversification at locus 154 (154_2).…”
Section: Resultsmentioning
confidence: 94%
“…LAM5 spoligotype is also the most reported in Rio Grande do Sul, another state in Southern Brazil, however belonging to SIT93 34 . A parallel situation has been reported with SIT863 MDR-TB strains in Rio Grande do Sul, that was initially identified in prison establishments but is now responsible for the majority of MDR-TB cases in that state 37,41 . The presence of isolates from inmate individuals in the TB transmission chains supports the dissemination of strains between the general population and prison establishments and although the directionality is unclear at this point, the latter along with the entire prison system may act as reservoir of specific strains and promote a wider dispersion of specific clones 42 .…”
Section: Discussionmentioning
confidence: 64%
“…The 12nt insertion results in a duplication of four amino acids (QNNP) and was firstly described by Perizzolo et al, (2012)[5]. Following studies analyzing MDR strains from Rio Grande do Sul[69] also reported strains carrying on the 12nt insertion, and to our knowledge, this insertion was not described in any other region worldwide.…”
Section: Introductionmentioning
confidence: 75%